Integrating Project-Based Learning in Foundational Sciences through Course Level Projects (CLP): From Classroom to Expo - Geedipally, Vanaja Reddy; Nagamalla, Lavanya; Jahnavi Barma, Sai Durga (Journal of Engineering Education Transformations, 2025)
This study explores the integration of Course-Level Projects (CLPs) in freshman engineering education to bridge the gap between industry and academia and prepare students for Project-Based Learning (PBL). Addressing the problem of traditional theoretical teaching methods that fail to equip students with practical skills, our research hypothesizes that CLPs enhance the application of theoretical knowledge and develop industry-relevant skills. Study conducted at an engineering college-Hyderabad Institute of Technology and Management (HITAM) in South India, where we employed a phased approach, incorporating CLPs into Physics and Chemistry courses, with guidance from faculty and industry mentors. Data was collected through interviews and surveys, analyzed using thematic coding. Findings indicate that CLPs provide real-world experience, improve teamwork, and develop critical skills, thus effectively preparing students for PBL and professional careers. The results support our hypothesis, demonstrating that CLPs align academic learning with industry needs. Future research should investigate the long-term impact of CLPs on career progression and further refine this educational approach.